An Analysis of the Connectedness to Nature Scale Based on Item Response Theory - Pasca, Laura; Aragonés, Juan I.; Coello, María T. (Frontiers in Psychology, 2017)
The Connectedness to Nature Scale (CNS) is used as a measure of the subjective cognitive connection between individuals and nature. However, to date, it has not been analysed at the item level to confirm its quality. In the present study, we conduct such an analysis based on Item Response Theory (IRT). We employed data from previous studies using the Spanish-language version of the CNS, analysing a sample of 1008 participants. The results show that seven items presented appropriate indices of discrimination and difficulty, in addition to a good fit. The remaining six have inadequate discrimination indices and do not present a good fit. A second study with 321 participants shows that the seven-ítem scale has adequate levels of reliability and validity. Therefore, it would be appropriate to use a reduced version of the scale after eliminating the items that display inappropriate behaviour, since they may interfere with research results on connectedness to nature.